Afghanistan's Geopolitical and Geo-economic Significance in Regional Connectivity and Development - YAR, Fayaz Gul Mazloum; ZAHID, Shamsurahman; MIAKHIL, Jan Mohammad (Journal of Political And Legal Sovereignty, 2023)
Purpose - The emergence of industrial hubs focused on oil and gas energy has fortified economic structures by integrating production, transit, and energy consumption, a phenomenon known as "geo-economics. The Near East, a strategic region rich in hydrocarbon reservoirs, has garnered significant attention as it seeks to influence critical areas, bases, and operational centers to achieve political-military and economic-commercial objectives. Due to its unique geographical location and proximity to major powers like Russia and China, along with regional players such as Iran, Pakistan, and India, Afghanistan assumes a vital operational role.Methodology - This article discusses the consequences of economic, geopolitical, and geo-economic developments in Afghanistan and neighboring regions using analytical and descriptive methods and reliable scientific and research sources. This research method has used the data and results of numerous studies in this field and explained these developments' connections and mutual effects.Findings - Capitalizing on its exceptional geographical position, Afghanistan stands to capitalize on numerous economic opportunities in trade and transit. Despite efforts to leverage this potential, significant progress remains elusive.Implication - This article delves into the economic and political prospects and capabilities engendered by Afghanistan's geographic position, aiming to identify its critical attributes for developmental purposes.